ARNOLD, Augustus Conrad [At] Inventory of documents - ARNOLD, Augustus Conrad [At] (ARCA, 2017)
Private papers of A.C. Arnold, Town Clerk, Windhoek, NP Member in the Council of SWA.
COVERAGE 1976-1987; 21 Files; 0,33 Metres.
Keywords: ARNOLD, Augustus Conrad [At]; Inventories; Politicians; National Party